Interactions of human milk oligosaccharides with the immune system - Slater, Alanna S.; Hickey, Rita M.; Davey, Gavin P. (Frontiers in Immunology, 2025)
Human milk oligosaccharides (HMOs) are abundant, diverse and complex sugars present in human breast milk. HMOs are well-characterized barriers to microbial infection and by modulating the human microbiome they are also thought to be nutritionally beneficial to the infant. The structural variety of over 200 HMOs, including neutral, fucosylated and sialylated forms, allows them to interact with the immune system in various ways. Clinically, HMOs impact allergic diseases, reducing autoimmune and inflammatory responses, and offer beneficial support to the preterm infant immune health. This review examines the HMO composition and associated immunomodulatory effects, including interactions with immune cell receptors and gut-associated immune responses. These immunomodulatory properties highlight the potential for HMO use in early stage immune development and for use as novel immunotherapeutics. HMO research is rapidly evolving and promises innovative treatments for immune-related conditions and improved health outcomes.